Wind Energy Conversion Systems Technology and Trends - Muyeen, S.M.; SpringerLink (Online service) (London : Springer London, 2012)
Wind Energy Conversion System covers the technological progress of wind energy conversion systems, along with potential future trends. It includes recently developed wind energy conversion systems such as multi-converter operation of variable-speed wind generators, lightning protection schemes, voltage flicker mitigation and prediction schemes for advanced control of wind generators. Modeling and control strategies of variable speed wind generators are discussed, together with the frequency converter topologies suitable for grid integration. Wind Energy Conversion System also describes offshore farm technologies including multi-terminal topology and space-based wind observation schemes, as well as both AC and DC based wind farm topologies. The stability and reliability of wind farms are discussed, and grid integration issues are examined in the context of the most recent industry guidelines. Wind power smoothing, one of the big challenges for transmission system operators, is a particular focus. Fault ride through and frequency fluctuation mitigation using energy storage options are also covered. Efficiency analyses are presented for different types of commercially available wind turbine generator systems, large scale wind generators using superconducting material, and the integration of offshore wind and marine current farms. Each chapter is written by a leader in the wind energy arena, making Wind Energy Conversion System a valuable reference for researchers and students of wind energy.
1. Introduction -- 2. Calculation Method of Losses and Efficiency of Wind Generator -- 3. Superconducting Direct Drive Wind Turbine Generators: Advantages and Challenges -- 4. Potential Applications and Impact of Most-Recent Silicon Carbide Power Electronics in Wind Turbine Systems -- 5. A New Interconnecting Method for Wind Turbine/Generators in a Wind Farm -- 6. Grid Connection Scheme of a Variable Speed Wind Turbine Driven Switched Reluctance Generator -- 7. Dynamic Model and Control of a Wind-Turbine Generator -- 8. Voltage Flicker Measurement in Wind Turbines -- 9. Grey Predictors for Hourly Wind Speed and Power Forecasting -- 10. Lightning Protection of Large Wind Turbine Blades -- 11. Lightning Surge Analysis on Wind Farm -- 12. Electric Grid Connections and Operational Aspects of Wind Power Generation -- 13. Application of Pumped Storage to Increase Renewable Energy Penetration in Autonomous Island Systems -- 14. Grid Frequency Mitigation Using SMES of Optimum Power and Energy Storage Capacity -- 15. Spacebased Observation of Offshore Strong Wind for Electric Power Generation -- 16. Power-Flow Control and Stability Enhancement of Four Parallel-Operated Offshore Wind Farms Using a Line-Commutated HVDC Link -- 17. Fault Ride Through of HVDC Connected Large Offshore Wind Farms -- 18. Connection of Large Off-Shore Wind Farms Using Diode Based HVDC Links -- 19. Wind Farm with HVDC Delivery in Inertial and Primary Frequency Response -- 20. HOTT Power Controller with Bi-directional Converter (HPB) -- 21. Transmission of Bulk Power from DC-Based Offshore Wind Farm to Grid Through HVDC System.
Keywords: Engineering; Renewable energy sources; Sustainable development; Engineering; Renewable and Green Energy; Renewable and Green Energy; Control; Sustainable Development